KL Vaccines against stis: where have we got to?. (13th September 2015) - Frazer, Ian
Abstract : STIs are an increasing global challenge for public health. Infections with HSV and with drug resistant gonococci are endemic, and chlamydial infection contributes extensively to reproductive problems, while immunosuppression from HIV infection has resulted in epidemic spread of XDR Tuberculosis. Antivirals have converted HIV to a chronic disease, and have helped to control HSV. However, the underlying infections are no less frequent. Immunisation is the single most effective public health measure after safe food and water, and has resulted in control of many previously epidemic viral infections, and eradication of smallpox. The universal HPV prophylactic immunisation program in Australia, has over eight years dramatically reduced the incidence of genital warts, and of cervical pre-cancer, amongst immunised and unimmunized young Australians. However, 60 years of effort have failed to produce an effective prophylactic or therapeutic vaccine against herpes viruses, despite genetic stability and multiple immunogenic viral protein antigens. Similarly, 20 years of efforts have produced vaccines with only limited impact on prevention of HIV infection. Recent successes with vaccines effective against systemic bacterial infections offer some prospects of success for bacterial STIs, while novel vaccine technologies offer similar promise for viral STIs, though the value proposition for industry will need to be developed. The health community will need to accept vaccine programs that are not so much for individual protection as strategies to reduce the community burden of disease, and to develop effective education strategies to encourage uptake of new vaccines as they are developed.